ANALISIS PERBANDINGAN KINERJA PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) : STUDI KASUS TERHADAP PT. PERTAMINA (PERSERO) - Rahman, Salma Athira (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2025)
In recent years, the sustainability trend has increasingly developed in all industrial sectors of the world. The sustainability aspect itself consists of three main components, namely environmental, social and governance or commonly known as ESG. The aim of this research is to analyze the comparison of company performance before and after the implementation of Environmental, Social and Governance (ESG) at PT. Pertamina (Persero). This type of research is qualitative with data collection techniques through interviews, observations and documents. The subjects in this research consisted of 5 sources, namely employees from the Sustainability Division in the Department of Strategy, Portfolio and Business Development (SPPU). The sampling technique used was purposive sampling and used 3 data analysis techniques, namely data reduction, data display, and conclusion drawing. The research results show that: 1) Before implementing ESG, it was still used as a CSR function in companies; 2) After implementing ESG, ESG provides many opportunities and benefits to companies; 3) Future plans, PT. Pertamina (Persero) will continue to develop and evaluate the results of implementing ESG performance in its company. Key Words: Company Perfomance, Environmental, Social, and Governance (ESG); PT. Pertamina (Persero)